Revenue Authorities : Issues and Problems in Evaluating their Success - Kidd, Maureen; Crandall, William Joseph (Washington, D.C. : International Monetary Fund, 2006)
Revenue authorities (RAs) have been adopted by some countries as an alternative delivery model for improved revenue administration. They are sometimes seen as a possible solution to problems such as low rates of tax compliance, ineffective tax administration staff, and corruption. The paper discusses RAs as a governance model, from the perspective of revenue administration and the almost universal desire to improve performance and compliance with the law. It compiles and analyses features of the model, examines reasons why revenue authorities were established, and explores the extent to which countries have evaluated the success of the model. It also assesses countries' own perceptions about how this model may have contributed to tax administration reform. Further, the paper discusses data collection difficulties in carrying out an assessment using econometric analysis, and the problem of attributing changes in performance to a particular governance model. The paper concludes that while there are subjective perceptions among countries with revenue authorities that their model has led to improved revenue administration and has spurred modernization, there is no objective analysis that countries with RAs have performed better in this regard than countries without RAs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet